2014
DOI: 10.1002/pamm.201410377
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Optimization Algorithms for Shape Optimization of Extrusion Dies

Abstract: The classical approach to extrusion die design relies heavily on the experience of the die designer; Especially the designer's ability to create an initial die design from a product design, the designer's constructional knowledge and performance during the running-in trials. Furthermore, the relative unpredictability of the running-in trials combined with the additional resource usage introduce uncertainties and delays in the time-to-market of a given product. To lower these delays and resource usage, extrusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…In particular, we assume that B and C can vary by ± 5 % about reference values B 0 and C 0 , respectively, and collect them in a parameter vector µ = [B, C]. To measure the homogeneity of the flow, a cost functional J as presented in [1] is used; it relates local velocity fluctuations to the overall average velocity. The relevant region, on which J will be evaluated, is the outlet of the extrusion die (see Fig.…”
Section: Reduced Flow Model For Plastics Meltmentioning
confidence: 99%
“…In particular, we assume that B and C can vary by ± 5 % about reference values B 0 and C 0 , respectively, and collect them in a parameter vector µ = [B, C]. To measure the homogeneity of the flow, a cost functional J as presented in [1] is used; it relates local velocity fluctuations to the overall average velocity. The relevant region, on which J will be evaluated, is the outlet of the extrusion die (see Fig.…”
Section: Reduced Flow Model For Plastics Meltmentioning
confidence: 99%
“…To solve the nonlinear, constrained optimization problem given by ( 24), two general types of algorithms can be distinguished, global derivative-free or local gradient-based methods [66][67][68]. While the advantages of the former are that they do not require implementation and evaluation of gradients and that they avoid local minima by searching the whole design space, the severe disadvantages in the context of nonlinear structural shape optimization are that convergence is slower, requiring many expensive function evaluations and, most importantly, that trial design vectors u may often lead to mechanically infeasible designs.…”
Section: Problem Formulationmentioning
confidence: 99%
“…Pauli et al [10] proposed the homogeneous die swell as objective function. Siegbert et al [11] demonstrated an optimization design method that profile shape was used as an objective function. Gifford [12] demonstrated a method of compensation for die swell in the design of profile extrusion die.…”
Section: Introductionmentioning
confidence: 99%